Story of my life - Score, Lucy (Bloom Books, 2025)
"Launching a brand new small town romance series from #1 New York Times bestseller Lucy Score. Romance novelist Hazel Hart seeks to overcome her writers block by leaving the big city to buy a house sight unseen in Story Lake, PA. The house comes with a spot on the town council and that's where the trouble begins"--